Introduction of Cationic Charge into DNA Near the Major Groove Edge of a Guanine•Cytosine Base Pair: Characterization of Oligodeoxynucleotides Substituted with 7-Aminomethyl-7-deaza-2′-deoxyguanosine. - Ganguly, Manjori; Ruo-Wen Wang; Marky, Luis A.; Gold, Barry (Journal of the American Chemical Society, 2009)
The article presents a study on the synthesis of 7-aminomethyl-7-deaza-dG in the creation of a structural model of groove associated cations. The structural model has been used to be able to reflect cation distribution and location which has been observed in DNA structures. The study reveals its findings on the spectroscopic and thermodynamic characterization of DNA.